Role of Non Government Organization (NGO) in Human Resource Development at Patnitala of Naogaon District in Bangladesh - Roy, Tapan Kumar; Rahman, Md Mosiur; Mondal, Shayampal Chandra (Socio-Economic Development Panorama, 2009)
The aim of this present study was to document the role of Non-Government Organization (NGO) in human resource development in Bangladesh. To reach the goal information was collected from 300 respondents by selecting three leading NGOs in Bangladesh BRAC, ASA and PROSHIKA. Descriptive and Multivariate logistic regression methods were employed in analyzing data. The data power out that respondent's monthly family income, expenditure and savings have increase after membership, one can say that there is a development in their latent potentialities along with human resource, which will bring forth sustainable development of the poor members. Regarding awareness about 54 percent of the respondents know something about AIDS, 82 percent of the respondents are well familiar about arsenic contamination, and about 63 percent of the respondents are able to acquire information about immunization programs after receiving membership to the NGO. With respect to sanitation facilitates 35 percent of them have increased for using toilet facilities, 54 percent of excessive respondents are using tube-well facilities only after involving in the NGO. From the above discussion, we uncover that more people have received sound sanitation facilities as compared to their previous status. This phenomenon was made possible due to NGO program. The findings reveal that NGO has trained their group members, how to prepare oral saline (66.33 percent). The multivariate logistic regression analysis that underline the model Illness of children of the members, leaving stool of the children, quality of the toilet, mother's TT vaccination and family income appears to the most influencing health variables. Likewise, the model opportunity of receiving primary education among the member's children is concerned to education, duration of membership, and for providing the model training opportunity of the members monthly family income that appears to the most influencing variables. NGO remains at a pivotal spot to reinforce the vitalities of the society towards the pathway to reach democratization and development climate. Key words: NGO, economic development, knowledge development, sanitation facilities, logistic regression analysis, AIDS Socio Economic Development Panorama; Vol. 1; No. 4, 2009; January-June